MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN POTENSI PEDAGOGIS GURU MTs. MAMBAUL ULUM BATA-BATA PAMEKASAN - Mohammad Safiuddin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Pedagogic competence is one type of competence that absolutely must be mastered by educators, pedagogic competence is a distinctive competence that will distinguish teachers and can determine the level of success of the process and learning outcomes of students. The formulation of the problems in the research included: The Pedagogical Potential of Teachers at MTs Mambaul Ulum Bata-Bata Pamekasan, management of madrasah principals in increasing the pedagogical potential of teachers, and supporting and inhibiting factors in increasing the pedagogical potential of teachers at Mts Mambaul Ulum Bata-Bata. This type of research was field research with a qualitative approach. Qualitative research itself is a research approach that uncovers certain social situations by describing reality correctly. The results showed as follows: First, the Pedagogical Potential of Teachers at MTs Mambaul Ulum Bata-Bata includes: Student Understanding, Learning Design, Educational Learning Implementation, Dialogic and Utilization of Learning Technology. Second, the Management of Madrasah Heads in Increasing the Pedagogical Potential of Teachers in MTs. Mambaul Ulum Bata-Bata, namely empowering the competencies possessed by teachers, the Teacher Working Group. The Three Supporting Factors in Increasing the Pedagogical Potential of Teachers in MTs. Mambaul Ulum Bata-Bata is the development of teacher pedagogic competencies, included awareness, interest and motivation of the teacher himself. While the inhibiting factors include the following: Qualification level of education, experience, facilities or facilities factor, and the role and support of the principal. Kompetensi pedagogic merupakan salah satu jenis kompetensi yang mutlak harus di kuasai pendidik, Kompetensi pedagogik merupakan kompetensi khas yang akan membedakan guru dan akan menentukan tingkat keberhasilan proses dan hasil pembelajaran peserta didiknyaAdapun rumusan masalah dalam penelitian antara lain: Pertama Potensi Pedagogis Guru Di MTs Mambaul Ulum Bata-Bata Pamekasan, Kedua Manejemen kepala madrasah dalam meningkatkan potensi pedagogis guru, Ketiga faktor pendukung dan penghambat Dalam Meningkatkan potensi Pedagogis guru Di Mts Mambaul Ulum Bata-Bata. Jenis penelitian ini adalah penelitian lapangan (field research) dengan pendekatan kualitatif. Penelitian kualitatif sendiri adalah pendekatan penelitian yang mengungkap situasi sosial tertentu dengan mendeskripsikan kenyataan secara benar. Adapun hasil penelitian ini sebagai berikut : Pertama Potensi Pedagogis Guru di MTs Mambaul Ulum Bata-Bata meliputi: Pemahaman Peserta Didik, Perancangan Pembelajaran, Pelaksanaan Pembelajaran yang Mendidik, Dialogis dan Pemanfaatan Teknologi Pembelajaran. Kedua Menejemen Kepala Madrasah Dalam Meningkatkan Potensi Pedagogis Guru Di MTs. Mambaul Ulum Bata-Bata yaitu memberdayakan kompetensi yang dimilki oleh guru, Kelompok Kerja Guru. Ketiga Faktor Pendukung Dalam Meningkatkan Potensi Pedagogis Guru Di MTs. Mambaul Ulum Bata-Bata ialah pengembangan kompetensi pedagogik guru antara lain; kesadaran, minat dan motivasi dari guru itu sendiri. Sedangkan faktor penghambatnya antara lain sebagai berikut: Kualifikasi jenjang Pendidikan, Pengalaman, faktor sarana atau fasilitas, dan Peran dan dukungan kepala sekolah.